Resection of posterior leaflet in reconstructive surgery of the mitral valve - S. I. Mokhnatyi; A. S. Zwyk; O. M. Dovhan (Ukrainian Journal of Cardiovascular Surgery, 2018)
This article analyzes the data of 56 patients with severe mitral insufficiency (MI) due to mitral valve prolapse (MVP) who underwent surgery in the period from January, 2011 to June, 2017 on the basis of GI “Scientific-Practical Children’s Cardiac Center”. All patients underwent reconstruction of MV using resection of the posterior leaflet. The plastics was successful in all patients right after surgery. The remote period of observation was from 6 to 72 months (average 32,3±15,3 months). Correction was final for all patients. 6 (10.7%) patients have a mild MI. Cases of moderate or severe MI during the follow-up were not registered. Cases of in-hospital mortality were not registered. Thus, though resection of posterior leaflet of MV is one of the first methods of MV plastics it is still a current surgical technique.